2019
DOI: 10.1111/tpj.14422
|View full text |Cite
|
Sign up to set email alerts
|

Phytoglobins in the nuclei, cytoplasm and chloroplasts modulate nitric oxide signaling and interact with abscisic acid

Abstract: Summary Symbiotic hemoglobins provide O2 to N2‐fixing bacteria within legume nodules, but the functions of non‐symbiotic hemoglobins or phytoglobins (Glbs) are much less defined. Immunolabeling combined with confocal microscopy of the Glbs tagged at the C‐terminus with green fluorescent protein was used to determine their subcellular localizations in Arabidopsis and Lotus japonicus. Recombinant proteins were used to examine nitric oxide (NO) scavenging in vitro and transgenic plants to show S‐nitrosylation and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 58 publications
1
39
0
Order By: Relevance
“…Physiological work using transgenic plants with altered concentrations of Glbs has shown that these proteins play an important role in plant development and morphogenesis, and largely supports the theory that they do so by modulating NO concentrations (Hill, ; Hebelstrup et al , ). Glbs may act through NO modulation to affect the signaling pathways of hormones including auxins (Elhiti et al , ), cytokinins (Ross et al , ; Wang et al , ), salicylate (Mur et al , ), jasmonates (Mur et al , ; Mira et al , ), ethylene (Mur et al , ; Kapoor et al , ; Hartman et al , ) and abscisic acid (ABA; Kapoor et al , ; Rubio et al , ). Two exemplary studies, concerning the response of Arabidopsis to biotic and abiotic stress, will illustrate the triple crosstalk between Glbs, hormones and NO.…”
Section: Globins Of Angiospermsmentioning
confidence: 99%
See 3 more Smart Citations
“…Physiological work using transgenic plants with altered concentrations of Glbs has shown that these proteins play an important role in plant development and morphogenesis, and largely supports the theory that they do so by modulating NO concentrations (Hill, ; Hebelstrup et al , ). Glbs may act through NO modulation to affect the signaling pathways of hormones including auxins (Elhiti et al , ), cytokinins (Ross et al , ; Wang et al , ), salicylate (Mur et al , ), jasmonates (Mur et al , ; Mira et al , ), ethylene (Mur et al , ; Kapoor et al , ; Hartman et al , ) and abscisic acid (ABA; Kapoor et al , ; Rubio et al , ). Two exemplary studies, concerning the response of Arabidopsis to biotic and abiotic stress, will illustrate the triple crosstalk between Glbs, hormones and NO.…”
Section: Globins Of Angiospermsmentioning
confidence: 99%
“…There is solid support for the NO scavenging reaction of Glbs in vivo . In Arabidopsis the reaction can be carried out by both Atha1 and Atha2 (Hebelstrup & Jensen, ; Kuruthukulangarakoola et al , ) and has been observed in stomatal cells, where a crosstalk between Glbs, NO and ABA may occur (Rubio et al , ). Recent work with Arabidopsis and barley has shown that NO can be ‘fixed’ into nitrogen metabolism in plants overexpressing, respectively, Atha1 or Atha2 (Kuruthukulangarakoola et al , ) and Hvul1‐1 (Zhang et al , ).…”
Section: Globins Of Angiospermsmentioning
confidence: 99%
See 2 more Smart Citations
“…Leghemoglobins (Lb) and symbiotic hemoglobins (sym‐Hb) are present in either legume species or actinorhizal/nonlegume symbiotic nodules, respectively. The presence of hemoglobin‐like proteins in organs not associated with symbiotic interactions led to the term nonsymbiotic hemoglobins (Hill, ; Rubio et al ., ). These nonsymbiotic hemoglobins are thought to function as key scavengers of NO under various environmental and stress conditions (Hill, ).…”
Section: Recommendations On Terminologymentioning
confidence: 97%